Q methodology and the measurement of subjectivity in corporate brand perception - G. Angelopulo (South African Journal of Business Management, 2009)
This paper reviews Q methodology and its application in an area of business research in which subjectivity is of considerable importance – that of corporate brand perception. More specifically, it explores the dimension of corporate brand perception that is directly related to the consumption and utilisation of the brand. The consumption-specific dimension of corporate brand perception is conceptualised as the `solution meaning of the corporate brand', and the process of identifying the solution meaning with the aid of Q methodology is described and applied in a case study.
Keywords: 650